Influences of slab fracturing techniques on long-term performance of rehabilitated PCC pavements. Issue 5 (16th April 2022) - Gu, Fan; West, Randy C.; Bowers, Benjamin F.; Willis, Richard
ABSTRACT: This study examined a specific pavement study (SPS-6) in the long-term pavement performance (LTPP) program to evaluate the influences of the three slab fracturing techniques, namely, crack and seat (C&S), break and seat (B&S), and rubblization on the performance of rehabilitated PCC pavements with asphalt overlays. Fourteen projects using a variety of PCC rehabilitation treatments were identified from the LTPP SPS-6 experiment, and the corresponding climatic data, traffic volume, layer thicknesses, back-calculated layer moduli, and performance data such as pavement smoothness, rut depth, longitudinal and transverse cracking were assembled. Two performance indicators, weighted annual average performance (WAAP) and average annual incremental performance (AAIP), were used to quantify the pavement performance. Statistical analysis results indicate that the C&S or B&S with a 20 cm asphalt overlay provided significantly better transverse cracking performance than a 10 cm asphalt overlay on PCC pavements. The rubblization technique nearly eliminated reflective cracking distress. A multiple linear regression model was developed to correlate design factors with the transverse cracking performance of rehabilitated PCC pavements. The layer thickness of PCC slab, modulus of fractured slab, modulus ratio of EPCC /EAC, and freezing index were identified as significant factors affecting the transverse cracking performance of C&S or B&S pavements.